PELAKSANAAN KEGIATAN PEMBERDAYAAN MASYARAKAT DALAM PENGELOLAAN SAMPAH MELALUI PROGRAM BANK SAMPAH OLEH DINAS LINGKUNGAN HIDUP DAN KEBERSIHAN KOTA PEKANBARU - Juliana, Septa; Andriyus, Andriyus (Universitas Muhammadiyah Tapanuli Selatan, 2023)
This study aims to determine the condition of the problem concerning the implementation of community empowerment activities in waste management through the Garbage Bank program in the city of Pekanbaru. This research uses a descriptive qualitative approach.with data collection techniques in-depth interviews, observational studiesinterview directly and in depth to the key informant who is considered to know the most. implementation of community empowerment activities in waste management related to the program being implemented.In general, the results of this study have been going well, seen from the application of the empowerment approach carried out through the 5Ps, namely: enabling, strengthening, protecting, supporting and maintaining, but there are still a number of things that need to be paid more attention, namely related parties to actively approach the community do not want to participate in the waste bank program so that there are still many people who dispose of waste in any place.